THE FACTORS OF EMPLOYEE TURNOVER INTENTION IN PRIVATE SECTORS ORGANIZATION IN JEDDAH, SAUDI ARABIA - Wajd Bashraheel; Malak Abunar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Despite that turnover is a major concern in determining the productivity of employees in accordance with their performance and some factors that has a major effect on turnover intention. The most of the organizations still not paying attention to this issue, and it is consequences on organization’s productivity, profitability, and quality. However, to retain the best employees; managers must ensure that their organizations meet expectations about rewards, working environment and productivity standards and then deliver on the promise. Employee turnover has been such a serious problem in Middle-East organizations, there is a few researches investigating it, especially studies on causes and consequences are scanty. This paper examines the causes of employee turnover, effects and suggests some strategies on how to reduce employee turnover within Saudi business setting. The study method selected was quantitative research approach and the data collection was adopted using a questionnaire. The questionnaire consists of 27 questions distributed to 110 respondents from private sectors organization with various professions in Jeddah. Based on this sample the results obtained indicate that turnover rate is decreasing in private sectors they are improving and this problem will affect organization’s productivity if not being resolved or decreased.